In situ net primary productivity of an Antarctic fast ice bottom algal community - Andrew McMinn; Ashworth, CM; Ryan, KG (2000)
Net primary production was measured in situ in an Antarctic fast ice bottom algal mat at Cape Evans, McMurdo Sound, Antarctica. Under-ice PAR irradiances between 18 November and 4 December 1997 were between 3 and 55 Î¼mol photons m-2 s-1. This produced a net oxygen export between 0.0084 and 0.0440 nmol O2 cm-2 s-1. Pmax was 0.034 nmol O2 cm-2 s-1, Ek was 14 Î¼mol photons m-2 s-1 the compensation point was approximately 2 Î¼mol photons m-2 s-1. These values are equivalent to a carbon-based production of 3.50 to 18.46 mg C m-2 h-1 and assimilation numbers of between 0.294 and 2.01 mg C mg-1 chl ah-1. Production levels on sunny days were so high that oxygen bubbles formed at the ice water interface and presumably contributed to the demise of the algal mat. Grazing by amphipods was also observed. While increasing net oxygen export was found to be strongly correlated with increasing irradiance, increasing under-ice current velocity was also found to increase production. The reduction in diffusive boundary layer thickness caused by increasing current velocity would have allowed both a more efficient transport of nutrients into the mat and a more efficient transport of oxygen away from the mat. Accumulation of sea ice algal biomass is not just a function of light but is also influenced by under-ice current velocity and possibly by oxygen build-up and grazing by amphipods and other invertebrates. In spite of the high under-ice irradiances reported from Cape Evans, loss mechanisms such as grazing and possibly oxygen toxicity were able to prevent the build-up of additional biomass.